Future time perspective in institutionalized adolescents - Carcelén Velarde, María Claudia (2008)
The study describes the future goals and concerns of institutionalized adolescents, and also identifies their attitudes towards the past, the present and the future, comparing them with a group of non-institutionalized adolescents with similar characteristics. It is a descriptive study with a transversal design, of 34 institutionalized and 41 non-institutionalized adolescents between 15 to 17 years old. The instruments were the Motivational Induction Method (MIM) and the Time Attitude Scale (TAS) (Nuttin, 1985). Goals are related to interpersonal contacts, the self-realization and the self. Institutionalized adolescents show more goals related to the development of aptitudes and a major necessity of interpersonal contacts associated with the fear of the damage caused by settling these relationships.